2008
DOI: 10.1093/jac/dkn213
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of antimicrobial usage in human and veterinary medicine in France from 1999 to 2005

Abstract: The same antimicrobial drugs were used in human and veterinary medicines but the quantitative patterns of use were different. Expression of antimicrobial usage is a key point to address when comparing usage trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 8 publications
1
48
0
7
Order By: Relevance
“…ceftiofur in animals and cefotaxime in humans, both belonging to the class of 3 rd generation cephalosporin drugs), most major classes of drugs are used in both human and veterinary medicine (Moulin et al, 2008). Classes of drugs solely used in veterinary medicine include feed additives such as ionophores, quinoxalines or bambermycins (Collignon et al, 2009).…”
Section: Overlap Of Antimicrobials Used In Veterinary and Human Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…ceftiofur in animals and cefotaxime in humans, both belonging to the class of 3 rd generation cephalosporin drugs), most major classes of drugs are used in both human and veterinary medicine (Moulin et al, 2008). Classes of drugs solely used in veterinary medicine include feed additives such as ionophores, quinoxalines or bambermycins (Collignon et al, 2009).…”
Section: Overlap Of Antimicrobials Used In Veterinary and Human Medicinementioning
confidence: 99%
“…Classes of drugs solely used in veterinary medicine include feed additives such as ionophores, quinoxalines or bambermycins (Collignon et al, 2009). When studying antimicrobial consumption in France, Moulin et al (2008) found that four antimicrobial classes were accounting for 80% of sales in veterinary medicine (tetracyclines, sulphonamides/trimethoprim, beta-lactams and aminoglycosides) whereas beta-lactam antimicrobials dominated in human medicine (accounting for more than 50% of the total consumption). As an example of overlapping use, WHO Criteria:…”
Section: Overlap Of Antimicrobials Used In Veterinary and Human Medicinementioning
confidence: 99%
“…Tetracycline resistance genes are often located on mobile elements such as plasmids, transposons and/or conjugative transposons, which can be transferred between bacterial species (Chopra and Roberts, 2001;Michalova et al, 2004). Studies on tetracycline resistance mechanisms are justified by data about tetracyclines being the far most frequently used antimicrobials in the EU (Schwarz and Chaslus-Dancla, 2001;Moulin et al, 2008;EMA, 2014).…”
mentioning
confidence: 99%
“…In addition to antimicrobial activity, some actinobacterial bacteriocins and their semisynthetic derivatives also exhibit anti-inflammatory [19][20][21], anti-allergic [20], antitumour [22][23][24] and antinociceptive activities [25,26], and may also act in blood pressure regulation [19,27]. Some of these peptides have already found clinical applications, such as thiostrepton, a thiopeptide used in dermatologic ointment for veterinary use [28], and others are in stages of pre-clinical and clinical trials, such as NAI-107, NAI-112 [29] and lancovutide/duramycin (https://clinicaltrials.gov/ct2/show/study/ NCT00671736?term=Lancovutide&rank=1; accessed September 17,2016), which reinforces the great potential of practical application of bacteriocins produced by Actinobacteria.…”
Section: Bacteriocins Produced By Actinobacteriamentioning
confidence: 99%